Leukodystrophies. Issue 4 (August 2022) - Adang, Laura
ABSTRACT: PURPOSE OF REVIEW: This article reviews the most common leukodystrophies and is focused on diagnosis, clinical features, and emerging therapeutic options. RECENT FINDINGS: In the past decade, the recognition of leukodystrophies has exponentially increased, and now this class includes more than 30 distinct disorders. Classically recognized as progressive and fatal disorders affecting young children, it is now understood that leukodystrophies are associated with an increasing spectrum of neurologic trajectories and can affect all ages. Next-generation sequencing and newborn screening allow the opportunity for the recognition of presymptomatic and atypical cases. These new testing opportunities, in combination with growing numbers of natural history studies and clinical consensus guidelines, have helped improve diagnosis and clinical care. Additionally, a more granular understanding of disease outcomes informs clinical trial design and has led to several recent therapeutic advances. This review summarizes the current understanding of the clinical manifestations of disease and treatment options for the most common leukodystrophies. SUMMARY: As early testing becomes more readily available through next-generation sequencing and newborn screening, neurologists will better understand the true incidence of the leukodystrophies and be able to diagnose children within the therapeutic window. As targeted therapies are developed, it becomes increasingly imperative that this broad spectrum of disorders is recognized and diagnosed. This work summarizes key advances in the leukodystrophy field.